Improvement of nutraceutical traits of banana: new breeding techniques - Tripathi, J.; Ntui, V.O.; Malarvizhi, M.; Muiruri, K.S.; Ravishankar, K.; Tripathi, L. (Springer, 2023)
Banana (Musa spp.) is an herbaceous, everlasting green monocotyledonous plant belonging to the family Musaceae. It is a major staple crop after rice, maize, wheat, potato and cassava, and it has a high potential to contribute to food and nutrition security. It is an excellent fruit full of micronutrients, especially vitamin A, iron, potassium, and magnesium, and is a source of energy for millions of inhabitants of tropical and subtropical regions. Despite these qualities, banana is still lacking in various essential nutrients. The conventional breeding program aims to increase the nutritional quality of banana. Still, the program is facing severe challenges due to the sterile seedless nature of banana and the narrow genetic diversity of several banana cultivars. Accessibility of well-annotated Musa genome sequences and established transformation and gene-editing platforms can contribute to developing banana with high dietary value. Furthermore, banana can produce edible vaccines, paving the way for future syringe-less vaccine development. This book chapter describes the various aspects of nutrition and the health-related importance of banana.